Strategies for habitat use among species of hunting spiders (Araneomorphae, Dionycha) in natural and artificial biotopes from southeastern Brazil - Rinaldi, Isabela M. P. (Acta Biológica Paranaense, 1996)
Foram estudadas 247 espécies de aranhas (Araneomorphae, Dionycha) dos estratos arbustivo e arbóreo de seis ecossistemas na região de Botucatu, São Paulo, Brasil, e sua coexistência foi analisada por meio de uma matriz de comunidade. Espécies relativamente abundantes são predominantemente generalistas, independente de seu ambiente; espécies representadas apenas por poucos individuos foram numerosas, e consideradas como membros marginais das comunidades. 0 coeficiente rnédio de interação comunitária foi estimado para cada espécie, assim como a covariação para as espécies mais abundantes em cada ecossistema. Há evidéncia de que a distribuição agregada de plantas favorece as espécies mais especializadas. Abstract Two hundred and forty seven species of dionychan spiders from the shrub and tree layers of six habitats in the region of Botucatu, State of São Paulo, Brazil, were studied, and their strategies for Coexistence were determined through construction of a community matrix. Spiders with relatively greater abundance behaved largely as generalists, independent of their environment, species represented by only a few individuals were numerous, and were considered to be marginal members of the communities. Estimates of the average community interaction coefficient for each species, and of covariation of the more abundant species in each ecosystem, indicate that the spiders avoid competition by spatial partioning, or by adopting differential strategies for habitat use, or because they belong to different guilds. In relation to the aggregate distribution of plants, species tend to specialization, and thus alter their strategy to follow the availability of resources in the environment. These results, together with accumulated knowledge of the ecology of spiders, lead to observations on the subgroup as agent of stabilization in insect populations. Résumé Un programme de prospection des araignées a été realisé dans la region de Botucatu (São Paulo, Brésil). Les strates arbustifs et arboricoles de six écosystèmes on été echantillonnés et 247 espèces dáraignées (Araneomorphae, Dionycha) ont été recueillies. Leur coexistence a été analyseé par one matrice de communauté. Les espèces relativament abundantes sont dans la grande majorité des especes généralistes, quelque que soit leur habitat. Beaucoup despèces avaient peu d'individus et peuvent être considdrées comme espêces marginales. Le coefficient moyen d'interaction de communauté a été estimé pour chaque espèce, aussi bien que la covariation pour les espéces les plus abondantes dans chaque ecosystéme. Nous avons aperçu que la distribution agrégeé des plantes rend evident la presence des espèces les plus specialiseés.